2020
DOI: 10.2147/jpr.s249134
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Characteristics of Postoperative Pain After VATS and Pain-Related Factors: The Experience in National Cancer Center of China</p>

Abstract: Purpose: No final conclusion has yet been reached on characteristics of postoperative pain and pain-related factors after video-assisted thoracoscopic surgery (VATS). This study was designed to explore features of acute severe pain and chronic post-surgical pain (CPSP), and the pain-related factors of VATS. Patients and Methods: Data of patients who underwent VATS for lung cancer in Cancer Hospital, Chinese Academy of Medical Sciences between March 2017 and January 2019 were reviewed in this retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
(30 reference statements)
1
25
0
Order By: Relevance
“…Previously published meta-analysis reported the incidence of CPSP after thoracotomy was 57%, but data about the risk of developing CPSP after VATS were not sufficient to summarize [3,15]. The reported incidences of CPSP after VATS range from 7.7 to 50% [1], apparently, our result ranks at a higher level of it. The relatively higher incidence may be explained by the definition of CPSP we used.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Previously published meta-analysis reported the incidence of CPSP after thoracotomy was 57%, but data about the risk of developing CPSP after VATS were not sufficient to summarize [3,15]. The reported incidences of CPSP after VATS range from 7.7 to 50% [1], apparently, our result ranks at a higher level of it. The relatively higher incidence may be explained by the definition of CPSP we used.…”
Section: Discussionmentioning
confidence: 57%
“…Chronic postsurgical pain (CPSP) is defined as chronic pain that develops or increases in intensity after a surgical procedure or a tissue injury and persists beyond the healing process, i.e., at least 3 months after the surgery or tissue trauma by International Classification of Diseases-11 (ICD-11) [ 1 ], and its incidence varies from 3 to 85% according to surgery type [ 2 ]. As traumatic as thoracotomy, the reported incidence of CPSP can be up to 57% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a faster recovery, less acute pain postoperatively, and a lower incidence of chronic pain. 11,12 Nonetheless, patients who undergo MICTS still frequently experience severe postoperative pain, [13][14][15][16] and the prevalence of PTPS after video-assisted thoracoscopic surgery (VATS) is still approximately 30%. 17 Multimodal pain management strategies have been championed as part of fast-tracked enhanced recovery after surgery (ERAS) programs to reduce the postoperative morbidity and mortality associated with poorly controlled pain and to address the multifactorial pathophysiology of thoracotomy pain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the postoperative acute pain is a predictive factor for the following chronic pain [18][19][20] , indicating that an e cient acute pain management contributes to prevent postoperative chronic pain. Exist evidences have supported the role of PVB to manage the neuralgia, myofascial thoracic pain, and chronic pain following thoractomy [21][22] .…”
Section: Discussionmentioning
confidence: 99%